The Prerequisites for D2C Strategies A Close View at Established Consumer Goods Manufacturers - Severin Lienhard; Marcus Schögel; Angela Boppart (Marketing Review St.Gallen, 2021)
Various drivers are currently encouraging established consumer goods manufacturers to start exploiting the D2C growth opportunity. Semi-structured interviews were used to explore the different facets and angles of D2C drivers and prerequisites. The results show that for traditionally intermediary-focused manufacturers the launching of D2C strategies demands four prerequisites: commitment, capabilities, customer transformation management and culture.
Keywords: 650